Kedudukan Harta Debitur yang Insolvensi Terikat dengan Perjanjian Leasing (Lex Jurnalica, 2010)
Leasing is a non-bank institutions that are of interest the private sector, through leasing is the private sector helped to finance his company budget constraint again. But how in the event of default by one party to a lease agreement. Status of debitur insolvency wealth tied up in the lease agreement can be openly expressed. In the lease agreement in general, the lessor (lender) is the owner of the goods leasing, the lessee (debitur) is a party that uses the asset or the lease of goods. Risks regarding the leasing of goods is also borne by the lease (debitor). Debtor’s insolvency protection in the property leasing agreement must still refer to protection provided for expressly by the legislation, which is seen in the main clause of the agreement. In the case of a state of insolvency occurs as a result of circumstance the lessee (debtor) who are in the state stops paying or not paying his debts, to settle that the lessee has filed a chord (accord). Curator acts a lessee has the right to directly engange in the management and control of an insolvency property lessor. As an alternative to resolve the insolvency of debtor property in the lease agreement Resistance, Appeals, and Review.Kata Kunci : Debitur, Insolvency, Leasing Agreement